Análisis de pérdidas de tiempo y sacarosa en el proceso de evaporación en agroindustrial laredo S.A.A., desde marzo hasta agosto del 2015 - Gamarra Torres, Román Filomeno (2016)
The present thesis titled"Analysis of time and sucrose losses in the evaporation process at agroindustrial laredo s.a.a from March to August 2015", had intended to analyze the time and sucrose losses in the evaporation process. The research work presents data of time and sucrose losses. The data were analyzed in two stages, the first time the loss of time and sucrose analyzed in the evaporation process, was conducted in March and April of 2015 operating just nine evaporators Robert in the evaporator station and the second time time losses and sucrose discussed in the evaporation area multi-reboiler evaporator with Robert evaporators nine station evaporation was conducted from June to August 2015 in operation. The results indicate a decrease in sucrose loss of 19.31% and 49.63% lost time. After comparing the data obtained in the statistical analysis, with a confidence level of 95%, it is shown that the study data analyzed leads to tell us that with the implementation of the evaporator multi-reboiler helped increase sugar production and reduce losses